Impact of Feeding Ration Partially Replaced by Rice DDGS on Reproductive Hormonal Profile and Performance in Gir Heifers - Gamit, Krishna C; Gadariya, Mahesh R; Savsani, Harish H; Odedara, Mulraj D; Vala, Karsan B; Sabapara, Ghanshyam P (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The effects of partial substituting rice distillers dried grains with solubles (RDDGS) for concentrate protein in the diet of 24 pre-pubertal/ pubertal Gir heifers (average b.wt. 166.29 ±11.21 kg, age 830.62±13.67 days) were studied over 180 days for reproductive hormonal profile and performance at University farm, Junagadh. The animals were randomly divided into three equal groups, each consisting of 8 heifers, viz., Control (100% crude protein (CP) from compounded concentrate mixture), T-1 (25% CP replaced with RDDGS) and T-2 (50% CP replaced with RDDGS). The basal diet of 10 kg seasonal green, dry fodder ad libitum and a mineral mixture @ 30 gm/h/d was given to the experimental heifers in addition to their daily and individual treatment diets. Heifers were fed a diet based on ICAR (2013) standards and the reproductive hormone levels in blood were measured on days 0, 90 and 180. The experimental heifers were daily observed for signs of estrus. Development and functioning of reproductive system of Gir heifers was assessed per-rectally at monthly intervals. Results showed that RDDGS increased progesterone levels, while estrogen remained unchanged. 75% of RDDGS-fed heifers exhibited earlier signs of puberty, with better reproductive tract development compared to the control group. Therefore, replacing 25% concentrate protein with RDDGS can be recommended for earlier puberty and improved reproductive performance in Gir heifers.
Keywords: DDGS; Estrus; Gir heifer; Ovarian structure; Reproductive hormones